Edvige Schettino l'eredità di una storica della Fisica - Esposito, Salvatore; Del Monte, Rosanna (Fuori collana, 2023)
In this volume, some friends and collaborators of Edvige Schettino remember her from both a professional and human point of view. The text is complementary to the volume, also published in December 2022 by FedOAPress, "Edvige Schettino. Dall'Aula di Rodi al Museo di Fisica: gli strumenti raccontano".